DNA fingerprinting at farm level maps rice biodiversity across Bangladesh and reveals regional varietal preferences. Issue 1 (December 2018) - Kretzschmar, Tobias; Mbanjo, Edwige; Magalit, Grace; Dwiyanti, Maria; Habib, Muhammad; Diaz, Maria; Hernandez, Jose; Huelgas, Zenaida; Malabayabas, Maria; Das, Subrata; Yamano, Takashi
Abstract The development, dissemination, and adoption of improved rice varieties are imperative for global food and nutritional security. Knowledge of the crop's distribution across agro-ecologies is important for impact assessment studies, varietal replacement strategies, and the development and implementation of agricultural policies. Bangladesh is the world's 4th largest rice producer. Though traditional varieties (TVs) are abundant and valued throughout Bangladesh, population growth and vulnerability to climate change, necessitate efficient deployment of high-yielding stress-tolerant modern varieties (MVs). To aid agricultural policy and strategy this study aimed to accurately assess the distribution of MVs and TVs across Bangladesh during the rainfed rice-growing season. Information derived from a survey of rice production areas were compared and combined with DNA fingerprinting information from the same locations. Biodiversity of Bangladesh rice remained high. While TVs and first generation MVs of Bangladeshi and Indian origin were still commonly grown, recently released stress-tolerant MVs were adopted in large proportions in several districts. Although farmers successfully distinguished TVs from MVs grown in their fields, a considerable lack of authenticity among MVs was observed, pinpointing shortcomings in the seed supply chain. This study identifies focal points for extension work and validates DNA fingerprinting as reliable method for impact assessment studies.